Environmental remediation promotes the restoration of biodiversity in the Shenzhen Bay Estuary, South China. Issue 1 (31st December 2022) - Xu, Hualin; Liu, Ke; Ning, Tianzhu; Huang, Gu; Zhang, Qianmei; Li, Yuelin; Wang, Mengqi; Fan, Yiming; an, Weili; Ji, Lingbo; Guo, Qinfeng; Ren, Hai
ABSTRACT: Background: Rapid urbanization has greatly changed land-use patterns in many estuarine areas around the world, including the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) resulting in serious water pollution and ecosystem degradation. Shenzhen City has conducted comprehensive ecological management and restoration in the Shenzhen Bay since 2007. The natural vegetation consisting of mangroves, semi-mangroves, wetland plants, and terrestrial plants were restored from the bund to the inner bank of the Fengtang River. Rain and sewage flow diversion systems were established. The non-point source and point-source sewage are now treated in municipal sewage treatment plants, then naturally flow through the constructed wetland, and then through a natural wetland, restored natural embankment, and finally through mangrove communities substantially improving water quality. Result: The restoration of the wetland has increased animal and microbial diversity and has supported the establishment of a complex and stable food web. With water purification and habitat restoration, the number of alien invasive plants in the estuarine ecosystem has decreased, and the diversity of native species of birds, fish, macrobenthos, amphibians, and reptiles has increased. Conclusion: These improvements indicate that human beings and nature can coexist in support of the sustainable development of Shenzhen City.